Staff Guidance Note on the Application of the Joint Fund-Bank Debt Sustainability Framework for Low-Income Countries. (Policy Papers; Policy Paper ;, 2008)
The objective of the joint Fund-Bank debt sustainability framework for low-income countries is to support LICs in their efforts to achieve their development goals without creating future debt problems. Countries that have received debt relief under the Heavily Indebted Poor Countries (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI) need to be kept on a sustainable track. Under the framework, country DSAs are prepared jointly by Bank and Fund staff, with close collaboration between the two staffs on the design of the macroeconomic baseline, alternative scenarios, the debt distress rating, and the drafting of the write-up.a.